Relação entre a suplementação de leucina e a sarcopenia - Rossetto, Marcelle Xavier Lacout (2011)
The loss of muscle mass is a major contributor to the limitation of movement, strength and functional capacity in aging. Because of this, sarcopenia has become the subject of many studies that seek to identify their causes and minimize their effects for a better quality of life for seniors. Currently, the branched chain amino acids, especially leucine, have been suggested as a strategy to combat muscle atrophy in terms of their relation to muscle protein metabolism. This study investigated the relationship between intake of leucine in the process of sarcopenia. To this end, we used 40 mice Mus musculus, aged 12 months, divided into four groups: control group (CG), leucine group 1 (GL1), leucine group 2 (GL2) and leucine group 3 (GL3), which received leucine supplementation in the diet ad libitum (0.042 g leucine / 5 g diet / day, 0.055 g leucine / 5 g diet / day and 0.063 g leucine / 5 g diet / day), respectively. Animals were euthanized by halothane inhalation. The gastrocnemius muscle was removed and these samples were analyzed by the colorimetric method of Lowry for the total protein and, histologically using hematoxylin-eosin staining to highlight the levels of muscle atrophy. The analysis of body mass was performed by weighing the initial and final times of the experiment (90 days). The results were subjected to analysis of variance for multiple comparisons between groups (ANOVA), post hoc Tukey, t test and nonparametric chi-square. Values were considered significant when p ≤ 0.05. The results show that it was possible to verify significant differences in average protein concentration between groups, ie, the GL has a mean concentration of protein significantly lower compared to the GL 2 and GL 3. It was identified that the level of muscle atrophy and the groups are significantly associated, as in the groups GL 2 GL 3 and the percentage of mice without atrophy is superior. With respect to body mass was significantly reduced only in the CG compared before and after treatment, suggesting that there was greater preservation of body mass in groups supplemented with leucine. Based on these results it is concluded that supplementation with leucine, at supraphysiological doses, of a positive influence on muscle protein metabolism, assisting in the preservation of the diameter of muscle fibers and subsequent maintenance of body weight. Thus, it is suggested that leucine supplementation can be used as a strategy to mitigate the effects of sarcopenia, as well as therapeutic support during rehabilitation of elderly people